Introducing future studies to ECON 101 students - Jahangir, Junaid (My University, 2022)
The objective in this paper is to introduce ECON 101 students, who usually learn about stylized neoclassical economics models, to the pressing issues of our times including climate change and economic inequality. In this regard a review of the book, Making Sense of the Future by interdisciplinary scholar, Rick Szostak, is undertaken and paired with ancillary material based on videos and articles. Students will learn that working for a better future does not mean a lifetime of limitless sacrifice, and that they can use their education to push for meaningful change in the world.
Keywords: future studies; ECON 101; teaching economics